Surveillance of Haemophilus influenzae among respiratory tract samples of Turkish children - KARAHASAN, AYŞEGÜL; ÜLGER, NURVER; İLKİ, ZEYNEP ARZU (My University, 2003)
We conducted three prospective studies of Haemophilus influenzae in different groups of children. Pharyngeal swab samples were taken (i). from 1382 healthy infants and children between 0 and 10 years of age (group 1), attending well child clinics (n=438), day care centres (n=440) and elementary schools (n=504), and (ii). from 322 children aged 2-10 years (group 2), clinically diagnosed as having upper respiratory tract infection. Pharyngeal swab samples and sinus aspirates were obtained from 49 children between 2 and 9 years of age (group 3), clinically diagnosed as having sinusitis. H. influenzae was isolated in similar rates from 315 (22.7%) of children in group 1, 72 (22.3%) of children in group 2 and 12 (24.4%) of children in group 3. Serotype b comprised 7, 5.2 and 2% of all H. influenzae isolates for group 1, 2 and 3, respectively. Production of beta-lactamase was detected in 1.0% of H. influenzae type b isolates in group 1, 1.2 and 6.1% of all isolates in group 2 and 3, respectively. There were no beta-lactamase negative ampicillin-resistant strains.
Keywords: Humans; Turkey; Child; Child, Preschool; Drug Resistance, Bacterial; Respiratory Tract Infections; Pharynx; Haemophilus Infections; Haemophilus influenzae; beta-Lactamases; beta-Lactam Resistance